Process writing : evaluation of its implementation in four Limpopo schools - Mamabolo, Joseph Thabang (My University, 2020)
This study evaluated the application of the ‘process approach’ to writing in secondary schools in Limpopo Province; The initial plan was to involve two rural and two urban schools. However, the urban schools did not cooperate as initially promised when preparations were made. It is for this reason that the sample was made up of two rural and two peri-urban schools. The study investigated English writing as a basic language skill that second language learners needed to acquire, in a process writing context. Related literature was reviewed to develop knowledge in the area of writing as a process. An exploratory research design was employed and a qualitative approach was followed to mainly collect in-depth data in a Grade 12 English language classroom. The Grade 12 learners and their teachers were interviewed and observed in their writing classrooms. The process that learners followed when engaged in writing an assigned essay was scrutinized in line with what is required by Curriculum and Assessment Policy Statement (CAPS) in order to confirm the teachers’ responses and the observations made during writing lessons. Thematic analysis was used for the data emanating from interview responses, an observation checklist and the learners’ essay marking rubric. The study revealed that the method of teaching writing and the learners’ writings resembled the process approach. This implies that teachers and learners implement process writing even though the teachers do so to a varying degree due to overcrowded classrooms and a lack of resources experienced more in rural schools than in the peri-urban ones
Thesis (M. A. (English Studies)) -- University of Limpopo, 2020
Keywords: Writing; Limpopo schools; Academic writing; Basic writing (Remedial education); English language - Writing